An introduction to the poetic books of the Old Testament (the wisdom and songs of Israel) - Bullock, C. Hassell (Chicago, IL Moody, 1988)
Includes bibliographical references and indexes.
Keywords: Bible. O.T. -- criticism, interpretation, etc; Hebrew poetry, Biblical -- history and criticism; Wisdom literature, Biblical -- history and criticism